2010
DOI: 10.4103/0189-6725.70417
|View full text |Cite
|
Sign up to set email alerts
|

Alvarado score as an admission criterion in children with pain in right iliac fossa

Abstract: Patients with equivocal signs can present a diagnostic challenge and are very often admitted to the surgical department for observation. The Alvarado score can be used as a scoring system that help in taking the decision for admission of cases with suspected acute appendicitis especially by primary healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…17 The assessment of abdominal pain may be amenable to such an intervention, and a major attractions of the Alvarado Score is that it can be tabulated into a routine clerking sheet. 18,19 However, our study has shown that using the Alvarado score, more than one-quarter of all patients with proven acute appendicitis would have been classified as having a low to intermediate probability of the disease being present and that slightly less than 5% of these patients would have been discharged home despite having the disease. The implications of this finding for staff in rural district hospitals are unclear.…”
Section: Limitationsmentioning
confidence: 72%
“…17 The assessment of abdominal pain may be amenable to such an intervention, and a major attractions of the Alvarado Score is that it can be tabulated into a routine clerking sheet. 18,19 However, our study has shown that using the Alvarado score, more than one-quarter of all patients with proven acute appendicitis would have been classified as having a low to intermediate probability of the disease being present and that slightly less than 5% of these patients would have been discharged home despite having the disease. The implications of this finding for staff in rural district hospitals are unclear.…”
Section: Limitationsmentioning
confidence: 72%
“…The Alvarado score discriminated well as an observation/admission criterion (cut point of 5) by achieving high pooled sensitivity of 99% overall (n = 28 studies, [5,8,10,) and in studies where data were available, it also performed well in the subgroup analysis for men, woman and children (pooled sensitivities: 0.96 for men, n = 5 [23,30,[33][34][35]; 0.99 for women, n = 5 [23,30,34,35,43] and 0.99 for children, n = 9 [10,21,23,27,28,30,[40][41][42]) ( Table 2 and Additional file 1 - Figure S1). In patients presenting with higher Alvarado scores (cut point of 7, the criterion for surgery), pooled diagnostic accuracy results had more limited clinical value (pooled specificity for all studies 0.82, n = 29, [5,8,10,11,[18][19][20][21][22][23][24][25][27][28][29][30][31][32][34][35][36]…”
Section: Diagnostic Accuracy Of the Alvarado Scorementioning
confidence: 88%
“…In patients presenting with higher Alvarado scores (cut point of 7, the criterion for surgery), pooled diagnostic accuracy results had more limited clinical value (pooled specificity for all studies 0.82, n = 29, [5,8,10,11,[18][19][20][21][22][23][24][25][27][28][29][30][31][32][34][35][36][37][38]41,42,[44][45][46][47]), with pooled specificities ranging from 0.57 for subgroup analysis of men (n = 6, [9,23,30,34,35,45] Figure S1). Overall, heterogeneity was high when all studies were included and was particularly high in the children subgroup as indicated by the variance logit transformed sensitivity and specificity (Table 2) and the prediction ellipses on the SROC curves Additional file 1 - Figure S1).…”
Section: Diagnostic Accuracy Of the Alvarado Scorementioning
confidence: 99%
“…Interestingly, their reported statistical analysis was based on an Alvarado threshold of 6, and was based upon 2 different outcomes; 1) performance of appendectomy and 2) histology. Using the standard threshold of 7 and including all comers related to histologic diagnosis, the sensitivity and specificity were 86% and 83% respectively (Shreef, Waly, Abd-Elrahman, & Abd Elhafez, 2010). Several attempts have been made to modify the Alvarado Score to improve its accuracy.…”
Section: The Alvarado Score (Mantrels)mentioning
confidence: 99%